2017
DOI: 10.1136/bmjopen-2016-014038
|View full text |Cite
|
Sign up to set email alerts
|

Associations of apolipoprotein B/apolipoprotein A-I ratio with pre-diabetes and diabetes risks: a cross-sectional study in Chinese adults

Abstract: BackgroundApolipoprotein B/apolipoprotein A-I (ApoB/ApoA-I) ratio is a useful predictor of cardiovascular risk. However, the association between the ApoB/ApoA-I ratio and the risk of type 2 diabetes mellitus (T2DM) is still obscure.AimsTo investigate the associations between the ApoB/ApoA-I ratio and the risk of T2DM and pre-diabetes in a Chinese population, and to assess the role of gender in these associations.MethodsA stratified random sampling design was used in this cross-sectional study which included 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…While this is the first study in GDM postpartum in relation to type 2 diabetes development, a number of studies in the general population have prospectively explored the relationship between Apo levels with incident diabetes. Apo AI levels [9,10], Apo B levels [11][12][13], Apo CIII levels [16,18], Apo E levels [16], Apo B/Apo AI ratio [12,14,15], Apo E/Apo AI ratio [16] and Apo CIII/Apo AI ratio [16] have all been found to independently predict the development of type 2 diabetes. Most of these earlier studies focussed on Apo AI and Apo B levels only and did not study other Apo species; mainly due to the unavailability of standardised clinical immunoassays [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While this is the first study in GDM postpartum in relation to type 2 diabetes development, a number of studies in the general population have prospectively explored the relationship between Apo levels with incident diabetes. Apo AI levels [9,10], Apo B levels [11][12][13], Apo CIII levels [16,18], Apo E levels [16], Apo B/Apo AI ratio [12,14,15], Apo E/Apo AI ratio [16] and Apo CIII/Apo AI ratio [16] have all been found to independently predict the development of type 2 diabetes. Most of these earlier studies focussed on Apo AI and Apo B levels only and did not study other Apo species; mainly due to the unavailability of standardised clinical immunoassays [19].…”
Section: Discussionmentioning
confidence: 98%
“…High Apo B levels have also been associated with incident type 2 diabetes in Aboriginal Canadians [11], Koreans [12] and Turkish women [13]. Moreover, multiple studies have shown that an increased Apo B/Apo AI ratio is associated with incident type 2 diabetes [12,14,15]. Recently, high serum Apo CIII and Apo E levels and Apo E/Apo AI and Apo CIII/Apo AI ratios were associated with incident type 2 diabetes in 971 individuals from the Rotterdam Study [16].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from previous research showed that apoB and apoA1 levels were superior to total cholesterol and low-density lipoprotein cholesterol (LDL-C) in predicting the future risk of fatal myocardial infarction [ 2 ]. Epidemiological studies have also demonstrated that apolipoproteins and the apoB/apoA1 ratio represent potential risk factors for the development of type 2 diabetes mellitus (T2DM) [ 3 ], insulin resistance [ 4 ], non-alcoholic fatty liver disease [ 5 ], metabolic syndrome [ 6 ], and cancer [ 7 ]. Multiple adverse health outcomes have been linked to low apoA1 levels, high apoB levels and high apoB/apoA1 ratios, leading to interest in developing strategies to manage abnormal apo variables for the prevention or treatment of associated metabolic and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in apoB/apoA1 ratio has been shown to be associated with cardiovascular disease progression. An increased ratio of apoB/ apoA1 has been found in previous studies in chronic illnesses such as diabetes, coronary artery disease and some chronic inflammatory diseases including RA [10,11,30]. There are no previous studies in the literature evaluating apoB/apoA1 ratio in Behçet's patients.…”
Section: Discussionmentioning
confidence: 90%
“…Apolipoproteins are one of the major components of lipoproteins, apolipoprotein B (apoB) is found atherogenic lipoproteins like low-density lipoprotein (LDL) and very low-density lipoprotein (VLDL), while apolipoprotein A1 (apoA1) is found in the structure of the anti-atherogenic cholesterol high-density lipoprotein (HDL). That is why an increase in apoB/apoA1 ratio is considered to be related to progression of cardiovascular disease and a tendency for atherosclerosis [10,11].…”
Section: Introductionmentioning
confidence: 99%